Ativismo no Sistema Interamericano de Direitos Humanos: a mobilização peruana como outlier nos casos de justiça de transição - Guimarães, Iara Rocha (2019)
Based on the comparison made only between the South American countries, it is noted that Peru is the State with the highest number of cases of human rights violations processed by the Inter-American System on Human Rights (IASHR) in the region. This is largely due to the interest and particular organization of Peruvian society to denounce the crimes committed during the internal armed conflict and the Fujimori government as a way to achieving political changes regarding the rights to truth and justice denied between 1980 to 2000. This research will be guided by the following questions: why and how did the victims and their families mobilize to report to the IASHR cases of human rights violations that occurred between 1980 and 2000 in Peru? Is there a pattern in the arguments used and in the goals sought by individuals in petitions? To answer them, the analysis will be concentrated on the mobilization carried out by individuals in Peruvian cases brought to the IASHR and will be done through theoretical-empirical research. Process-tracing will be used as a methodological contribution to analyzing the reasons that have made individuals more successful in triggering and having their cases analyzed by the IASHR compared to domestic and international NGOs that, according to the literature, should be the most successful as a result of their expertise.